The Effect of Green Accounting Implementation and Asset Turnover on Corporate Value in Manufacturing Sector Companies on the Indonesia Stock Exchange - Tampubolon, Michael Saputra; rahmadhani, sarinuzullina (TALENTA PUBLISHER UNIVERSITAS SUMATERA UTARA, 2023)
This study aims to determine the effect of green accounting as measured by the PROPER performance rating of the Ministry of Environment and Assets Turnover as measured by Total Assets Turnover (TATO) on firm value (PBV). Sampling was carried out using a purposive sampling method with manufacturing sector companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2020 period. The data analysis technique used in this study is multiple linear regression analysis. The results of this study conclude that the application of green accounting has a positive and significant effect on corporate value and asset turnover has a positive and significant effect on corporate value.